A Case of Solitary Necrotic Nodule Treated with Laparoscopic Hepatectomy: Spontaneous Regression of Hepatocellular Carcinoma?. (19th March 2013) - Tomishige, Hirokazu; Morise, Zenichi; Mizoguchi, Yoshikazu; Kawabe, Norihiko; Nagata, Hidetoshi; Ohshima, Hisanori; Kawase, Jin; Arakawa, Satoshi; Yoshida, Rie; Isetani, Masashi
Abstract : Solitary necrotic nodule of the liver is a rare benign lesion with a completely necrotic core and a hyalinized fibrotic capsule containing elastic fibers. The pathogenetic mechanism is still unclear. We here describe a case of SNN, whose central reticulin fibers within the nodule suggest the origin as hepatocellular carcinoma or other hepatocyte-origin tumors, treated with laparoscopic anatomical segmentectomy of the liver. A 76-year-old Japanese female, with no prior medical history and no symptom, visited our hospital with the heterogeneous hypoechoic lesion in the liver segment VI incidentally pointed out in abdominal ultrasonography. Computed tomography with contrast demonstrated a 1.1 cm sized low-density lesion with mild ring enhancement on the rim in the arterial phase. Since the possibility of malignant tumor with necrotic change could not be ruled out, she underwent laparoscopic anatomical segmentectomy of the liver. In the histological examination of the surgical specimen, the liver nodule was necrotic tissue without viable cells and signs of inflammation, which had fibrous capsule and central cystic change and showed trabecular pattern alignment of ghost cells and reticulin fibers orthogonal to the capsule. Also, the findings of chronic hepatitis were observed in the background liver.